2004
DOI: 10.1007/s10143-004-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences with oligoastrocytomas WHO grade II and III

Abstract: Between April 1991 and June 2002, 39 patients with an histologically proven oligoastrocytoma WHO grade II and III were operated on in our department. Twenty-two patients were male and 17 female. Mean age was 42 years (20-67 years). The tumor was localized in the frontal lobe in 22 patients, in the temporal lobe in seven patients, in the parietal lobe in nine patients and in the occipital lobe in one patient. The leading clinical symptoms were seizures in 33 patients. Seventeen patients were operated on under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…In our own series of OA in the general brain tumor population (Beckmann and Prayson 1997), the average age of presentation was 37 years. The median preoperative course, 10.5 years, was long compared to other OA series (Beckmann and Prayson 1997, Buhl et al 2004, Johannesen et al 2003, Whittle and Beaumont 1995. It has been established that patients suffering from tumor-related intractable epilepsy have a generally good prognosis, with an indolent course of their tumors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our own series of OA in the general brain tumor population (Beckmann and Prayson 1997), the average age of presentation was 37 years. The median preoperative course, 10.5 years, was long compared to other OA series (Beckmann and Prayson 1997, Buhl et al 2004, Johannesen et al 2003, Whittle and Beaumont 1995. It has been established that patients suffering from tumor-related intractable epilepsy have a generally good prognosis, with an indolent course of their tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Seizures occur in 63-85% of patients with OA as the initial presenting symptom (Tortosa et al 2003;Buhl et al 2004). Other common presenting symptoms included memory changes, headache, and speech difficulties (Buhl et al 2004). Very few studies have evaluated in any significant detail, the correlation between OA and patients who suffer from intractable epilepsy, necessitating neurosurgical excision of seizure foci.…”
mentioning
confidence: 99%
“…Histology of the metastasis showed glioblastoma. 5 The only reported case of direct spinal extension of oligoastrocytoma was by Kuroiwa, who reported a patient with a grade II cerebellar oligoastrocytoma extending in the subarachnoid space to the C2 level. 12 Leptomeningeal spread of tumour is an uncommon event and is diagnostically challenging in the absence of hard neurological or radiological evidence.…”
Section: Discussionmentioning
confidence: 98%
“…Leading presenting symptoms are seizures and headaches. [4][5][6] The mainstay of treatment today involves surgery, with adjuvant radiotherapy or chemotherapy being offered mostly in the setting of disease progression or malignant transformation. 4,7,8 Shaw et al reported a median survival time for grade II oligoastrocytoma of 7.1 years, with 5-year and 10-year survival rates of 63% and 33% in patients treated with surgery and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…"low-grade gliomas") und anaplastischeFormen unterteilt (3,13,19). Beim anaplastischen Oligoastrozytom wird beim Menschen eine aggressive Therapiekombination ausC hirurgie, postoperativerR adiotherapie undC hemotherapie durchgeführt (3,12). Über das biologischeVerhalten anaplastischer Oligoastrozytome desH undesi st bisherw enig bekannt ( 24).…”
Section: Diskussionunclassified